Peran Komite Audit Dalam Mempengaruhi Fee Audit, Audit Tenure, Rotasi Audit Dan Reputasi Auditor Terhadap Kualitas Audit - Gilang Abytia Eka Gunawan; Fatchan Achyani (STIE Amkop Makassar, 2024)
The consideration of audit quality is essential to ensure the credibility and usefulness of a company's financial statements for financial statement users. Companies frequently encounter factors that can impact the quality of their audits. The objective of this study is to assess the impact of audit fees, audit tenure, audit rotation, and audit reputation on audit quality in financial sector companies listed on the IDX throughout the period of 2019-2022. The study also seeks to examine the role of the audit committee as a moderator in this relationship. The study employed a purposive sampling strategy to choose a sample, resulting in 41 companies and 164 research data points. Conducting data testing with the application of moderation regression analysis. The findings indicated that both audit fees and audit reputation exerted a substantial impact on the quality of audits. However, audit tenure and the process of rotating auditors do not influence the quality of the audit. The audit committee lacks the ability to moderate the impact of all independent variables on audit quality.